Magnetron Discharge in the Diode with a Liquid-Metal Target; 7 International conference on modification of materials with particle beams and plasma flows - Zhukov V. V.; Kosmin D. M.; Krivobokov V. P. Valery Pavlovich; Yanin S. N. Sergey Nikolaevich (Modification of material properties, 2004)
Title from the title-page.